The Effectiveness of Dynamic Problem-Solving Strategy and Innovative Assessment Tools to Improve Students’ Higher-Order Thinking Skills - Haris, Abdul; Hasyim, Mutahharah; Ma'ruf; Halim, Anis Diyana; Mahir; Ramadhan, Imam (Jurnal Pendidikan IPA Indonesia, 2025)
Education in Indonesia continues to face challenges in developing students' Higher-Order Thinking Skills (HOTS) to achieve Sustainable Development Goals (SDGs) 4 on quality education, which requires new strategies such as Dynamic Problem Solving (DPS) and innovative assessment tools to improve critical and analytical reasoning. This study aims to measure the DPS strategy and innovative assessment tools in improving students' HOTS  in physics learning. This research method uses a quasi-experiment with a posttest-only control group design. This study involved 120 high school students from four regencies/cities in South Sulawesi, Indonesia. Data on the effectiveness of the DPS strategy were collected and analyzed using an independent t-test, and data on innovative assessment tools were collected and analyzed through validity and reliability tests. The results of the HOTS test of students after participating in physics learning using the DPS strategy and innovative assessment tools showed that the experimental group was better than the control group. This study concludes that implementing the DPS strategy and innovative assessment tools effectively improves high school students' HOTS through physics learning. This research has an impact in encouraging critical and analytical thinking in students to solve real problems. In addition, this research also contributes to being a reliable and robust new pedagogical approach in physics learning under the demands of 21st century education.